Child Eveningness as a Predictor of Parental Sleep - Hanni Rönnlund; Marko Elovainio; Irina Virtanen; Anna-Riitta Heikkilä; Hanna Raaska; Helena Lapinleimu (MDPI AG, 2022)
Child eveningness has been associated with many adverse outcomes for children. The aim of this study was to assess whether child eveningness poses a risk to parental sleep quality in follow-up. A total of 146 children (57% adopted, 47% boys, mean age at follow-up 5.1 years [standard deviation 1.7]) completed a 1-week actigraph recording to analyze their sleep twice, 1 year apart. The parents completed the Child ChronoType Questionnaire for their child and a short version of the Morningness-Eveningness Questionnaire for themselves and the Jenkins Sleep Scale for their sleep quality. Linear regression analyses showed that subjective parental sleeping problems at baseline were associated with subjective parental sleeping problems at follow-up. A morning-type child decreased the risk of parental sleeping problems at the 1-year follow-up compared to the child evening chronotype. Additionally, the child intermediate chronotype decreased the risk of maternal sleeping problems at the 1-year follow-up compared to the evening chronotype of the child. Parents of evening-type children experienced more sleeping problems in the follow-up, compared to parents of morning-type children. This finding encourages parents and professionals to steer the diurnal rhythm of evening-type children toward an earlier daily routine.